Бандеровский схрон: [роман] / Александр Тамоников - Тамоников Александр Александрович (СМЕРШ - спецназ Сталина, 2017)
Экземпляры: ф.8 (20201009) / Инвентарный номер: 60349 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Т 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44